Suitable endometrial thickness on embryo transfer day may reduce ectopic pregnancy rate and improve clinical pregnancy rate - Shiming Wang; Lin Qi; Yaping Liu; Hao Shi; Xiaoli Chen; Ningning Wang; Yingchun Su (BMC, 2023)
Abstract Background This retrospective study aimed to investigate the most suitable endometrial thickness (EMT) on the day of embryo transfer that could reduce ectopic pregnancy rate (EPR) and improve clinical pregnancy rate (CPR) in fresh embryo transfer patients with early follicular phase long-acting regimen. Methods A total of 11,738 IVF/ICSI cycles, comprising 4,489 non-clinical pregnancies, 7,121 intrauterine pregnancies, and 128 ectopic pregnancy cycles after fresh embryo transfer, recorded between September 2017 and December 2020. Clinical pregnancy (CP) and ectopic pregnancy (EP) were the primary outcomes. Multivariate logistic regression was used to calculate the adjusted odds ratio (aOR) and 95% confidence interval (CI) for EP and CP. Patients were divided into three groups based on the EMT (6-10 mm, 11-15 mm, and 16-20 mm). CPR and EPR per millimeter of EMT were drawn into a line chart, and three groups were analyzed by Chi-square test. Results After controlling for potential confounders, EMT had a significant effect on CP (aOR = 1.07; 95% CI, 1.05-1.08; P = 0.00) and EP (aOR = 0.88; 95% CI, 0.82-0.94; P = 0.00). With the increase of EMT, CPR increased and EPR decreased. Pearson correlation coefficients were r = 0.708 (P = 0.00) and r =-0.558 (P = 0.03), respectively. Significant differenceswere detected in the CPRs and EPRs (all P = 0.00). The CPR in the 6-10 mm group (54.88%) was significantly lower than that in the 11-15 mm group (64.23%) and the 16-20 mm group (64.40%) (P = 0.00). The EPR in the 6-10 mm group (2.72%) was significantly higher than that in the other two groups (1.60% and 0.97%, P = 0.00). The difference in CPR and EPR between the 11-15 mm group and the 16-20 mm group was not statistically significant, which indicated that EMT ≥ 11 mm simultaneously reduced the EPR and increased the CPR. Conclusions EMT was inversely proportional to EPR and directly proportional to CPR in fresh embryo transfer cycles. The EMT ≥ 11 mm on the day of embryo transfer could simultaneously achieve lower EPR and higher CPR. Accordingly, more attention should be given to the EMT of women who underwent ART treatment.